"MY FEELINGS": UNDERGRADUATE STUDENTS' EMOTIONAL RESPONSES TOWARDS SUPERVISORS' WRITTEN CORRECTIVE FEEDBACK IN THEIR THESIS WRITING - Iis Trisdayanti; Neni Marlina; Nita Sari Narulita Dewi (TLEMC (Teaching and Learning English in Multicultural Contexts), 2019)
This case study aims to discover the undergraduate students' emotional response towards supervisors' Written Corrective Feedback (WCF) in their thesis and examine its impacts on their thesis writing process. This research was conducted at one university in Tasikmalaya, West Java, Indonesia by involving three undergraduate students as the participants. Semi-structured interview was used to collect data then it was analyzed using thematic analysis from Braun Clarke (2006). The results revealed that the emotional responses felt by students included positive emotional responses consisting of acceptance of feedback, satisfaction, and feeling of happiness; and negative emotional responses consisting of rejection of feedback, dissatisfaction, distraction, frustration, disappointment, and sadness. Meanwhile, its impacts on their thesis writing process were improving undergraduate students' consciousness in writing thesis, enthusing to complete the thesis immediately, and discontinuing writing thesis for a certain period of time.